Peristilahan Pengolahan Sagu dalam Bahasa Melayu Dialek Sambas, di Desa Sebangun, Kecamatan Sebawi, Kabupaten Sambas - Sarbini, Sarbini; Patriantoro, Patriantoro; Wartiningsih, Agus (Universitas Islam Sumatera Utara, 2025)
The sago processing activities in Sebangun Village, Sebawi District, exhibit a rich variety of terminologies that reflect the linguistic and cultural characteristics of the local Malay Sambas dialect. This study aims to identify and analyze the terminology used in sago processing within the Malay Sambas Dialect (MSD) community of Sebangun Village, Sambas Regency. The research employed a descriptive qualitative method, with data obtained from native Malay Sambas speakers who have experience in sago processing. Data collection was conducted through observation, interviews, recording, note-taking, and documentation. The collected data were analyzed through transcription, classification, analysis, and interpretation. The findings revealed 35 monomorphemic and 38 polymorphemic terms related to sago processing, categorized based on processing stages, tools and materials, and final products. The semantic analysis indicated that 35 terms carry lexical meanings, while 38 terms express grammatical meanings. Functionally, there are 29 terms related to processing procedures, 23 to tools and materials, and 24 to processing results. This study not only contributes to the preservation of local linguistic heritage but also serves as a pedagogical reference for developing Bahasa Indonesia learning modules, particularly in terminology and dialectology studies at the high school level.